2001
DOI: 10.1007/s15010-001-1134-6
|View full text |Cite
|
Sign up to set email alerts
|

Osteomyelitis: Etiology, Diagnosis, Treatment and Outcome in a Public versus a Private Institution

Abstract: Osteomyelitis patient outcome varies less by hospital setting than by case management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…Protocols would need to define the dosage, route of administration, and duration of antibiotic therapy. There are few data available on which to base these decisions, but in an era of highly bioavailable oral agents, there is little to support the recommendation to use intravenous drugs to initiate treatment [24,58]. Most agree that if surgery is withheld, antibiotics should be continued for 4-6 weeks or more [11,24].…”
Section: Studies To Determine the Relative Roles Of Medical And Surgimentioning
confidence: 99%
“…Protocols would need to define the dosage, route of administration, and duration of antibiotic therapy. There are few data available on which to base these decisions, but in an era of highly bioavailable oral agents, there is little to support the recommendation to use intravenous drugs to initiate treatment [24,58]. Most agree that if surgery is withheld, antibiotics should be continued for 4-6 weeks or more [11,24].…”
Section: Studies To Determine the Relative Roles Of Medical And Surgimentioning
confidence: 99%
“…Although cryptic infection itself may not cause any clinical problems, whenever the host defense mechanisms are suppressed (i.e. systemic diseases, hypersensitivity to metallic implants), the bacteria may be recalcitrant and cause the infection leading to implant failure (Lobati et al 2001). In our study, we found that the patients with internal fixations with plates and screws were at a higher risk of infection.…”
Section: Discussionmentioning
confidence: 55%
“…Since P. aeruginosa was frequently found in our study, we assumed that it was the main nosocomial pathogen in our operating theatre. Furthermore, this species was also classified as the main nosocomial pathogen in humans (S tein et al 1998;Lobati et al 2001;V alenziano et al 2002). The mixed bacteria identified from the samples before and after implantation were in the same incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Osteomyelitis is an inflammatory and infectious condition where Staphylococcus aureus is the most common infectious agent (Chihara and Segreti, 2010;Lew and Waldvogel, 2004;Lobati et al, 2001;O'May et al, 2011). Nowadays this disease is a public health problem with a significant morbidity and mortality (Lew and Waldvogel, 2004).…”
Section: Introductionmentioning
confidence: 99%